An episcopal puzzle: George Richmond’s monument to Bishop Charles James Blomfield (1859–67) - Whyte, W (Oxford University Press, 2022)
George Richmond’s memorial to Charles James Blomfield, Bishop of London between 1828 and 1856, is both important and puzzling. Yet it now attracts little attention. In Blomfield, it commemorates neither a famous hero nor an obviously notorious villain. Its creator, Richmond, was well known in his day, but has hardly retained his réclame. Even those who have sought to highlight Richmond’s importance are inclined to conclude that this example of his work is merely ‘well conceived and competently executed’.1 Dismissed by one expert guide as nothing more than a ‘routine marble figure on a sarcophagus’, the memorial’s form seems as conventional as its subject.2 Despite wholly filling a large niche in the south choir aisle of St Paul’s cathedral, the so-called Dean’s Aisle, it suffers from the comparison with its near neighbour, the far more striking – and infinitely more famous – effigy of a former Dean, John Donne, standing wrapped in his own shroud. Like so many of the other nineteenth-century statues in St Paul’s, the Blomfield memorial can now seem largely ‘mute and moribund’.3 Attended to more closely, however, it reveals itself to be a rather more interesting object: one that discloses intriguing paradox and real significance – not least for understanding the wider question of the cathedral’s place as a pantheon.